Regulation and Function of Lactate Oxidation in Streptococcus faecium - London, Jack (1968)
Regulation of the synthesis and function of an l(+)-specific lactate-oxidizing enzyme system found in a homofermentative Streptococcus was investigated. With the exception of fructose, aerobic growth at the expense of a variety of substrates resulted in the formation of a lactate oxidation system; anaerobic growth resulted in a marked reduction or complete loss of lactate-oxidizing activity. Growth on fructose, under aerobic and anaerobic conditions, invariably produced a decrease in the activity of the lactate oxidation system. A negative control, activated by an early intermediate product of glycolysis, appeared to be responsible for repression of the lactate-oxidizing enzyme(s). The enzyme system confers upon the organism the ability to grow aerobically at the expense of l(+)-lactic acid.